Tafsiran Hakikat Informasi dalam Era Teknologi Informasi: Tinjauan Konseptual dan Implikasinya - Muhajir, Ahmad (Universitas Ma'arif Nahdlatul Ulama Kebumen, 2024)
In the age of rapidly advancing information technology, it is crucial to have a thorough understanding of the nature of information to tackle the challenges posed by digital transformation. This article provides a comprehensive conceptual overview of the interpretation of the nature of information and its implications in the current context of information technology. This research explores the essence and fundamental nature of information by integrating views from various disciplines, such as philosophy, epistemology, and information technology. The focus of this research is on all forms of data, messages, and knowledge that are formed, exchanged, and processed in the context of information technology. This research aims to provide a better understanding of how information affects individuals, organizations, and society as a whole by examining aspects such as its existence, structure, value, and impact. The limitations of this study are focused on understanding the nature of information in the context of information technology and its implications for information practices and policies. The study employs a descriptive-analytical approach that combines literature analysis and conceptualisation to develop a comprehensive framework. The data sources used include scientific articles, books, and other related theoretical sources in the fields of philosophy, epistemology, and information technology. Through this in-depth analysis, the article offers insight into how a better understanding of information's nature can shape more effective information practices and policies in the face of challenges and opportunities presented by the digital revolution